HUBUNGAN ANTARA PENGUASAAN KALIMAT EFEKTIF DAN KEBIASAAN MEMBACA MEDIA MASSA CETAK DENGAN KETERAMPILAN MENULIS TEKS BERITA PADA SISWA KELAS VIII SMP NEGERI SE-KECAMATAN SERENGAN KOTA SURAKARTA - Novi Iswandari; Budhi Setiawan; Chafit Ulya (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This research is a quantitative research that aims to describe about the correlation between effective sentence mastery and reading habit of printed mass media with news text writing skills independent or together. The method used is correlational survey. The sample in this study is 126 students or 28% from the total population of 446 students. Thesample determined by cluster random sampling technique. Research data were obtained through three instruments (1) test of news text writing skills; (2) effective sentence mastery test; and(3) questionnaire of reading habit of printed mass media. Data analysis technique used is product moment correlation (simple and double) and regression. The result of this research show effective sentences mastery (X1) and reading habit of printed mass media (X2) together contributes 48% to news text writing skills (Y).